Faktor-Faktor yang Berhubungan Dengan Pemakaian Alat Kontrasepsi MKJP di Wilayah Kerja Puskesmas Kuta Baro, Aceh Besar - Nurmahlina Nurmahlina; Eva Purwita; Yushida Yushida (PT. Intelek Cendikiawan Nusantara, 2026)
The use of long-acting reversible contraception (LARC) is one of the most effective strategies to control population growth and improve maternal health. According to the World Health Organization (WHO), the global use of contraception among women aged 15–49 years increased from 47.7% in 2000 to 49.0% in 2023. However, the utilization of long-acting contraceptive methods is still relatively low compared to short-term methods. This study aimed to determine the factors associated with the use of long-acting reversible contraception (LARC) in the working area of Kuta Baro Community Health Center, Aceh Besar. This research used an analytical survey with a cross-sectional design. The population consisted of couples of reproductive age who were family planning acceptors in the working area of Kuta Baro Health Center. A total of 93 respondents were selected using purposive sampling. Data were collected using a structured questionnaire and analyzed using the Chi-Square test. The results showed that there were significant relationships between age (p = 0.022), parity (p = 0.022), occupation (p = 0.000), and education (p = 0.000) with the use of long-acting contraceptive methods. In conclusion, age, parity, occupation, and education are significantly associated with the use of long-acting reversible contraception. Health workers are expected to provide more intensive counseling to increase the utilization of long-acting contraceptive methods among couples of reproductive age.